Cost-Effective and Sustainable Harvest Methods - Poikonen, Pasi; Iwarsson Wide, Maria; Laitila, Juha; Gudynaitė- Franckevičienė, Valda; Jakobson, Indrek; Luik, Allar; Pošlin, Livia; Gong, Peichen; Lazdiņš, Andis; Bermanis, Raimonds; Birkena- Dzelzkaleja, Maija; Grasmane, Elvira; et al. (Luonnonvarakeskus, 2020)
Forest biomass is a highly important source of renewable energy in the Baltic Sea Region. Forest harvests produce a huge amount of residues, of which a large share could be used for energy purposes but are currently often left in forests due to economic and ecological reasons. There is a large potential in tackling the increasing demand for renewable energy by increasing the harvest of logging residues and small trees in pre-commercial thinning. This handbook aims to increase production of renewable energy in the Baltic Sea Region by improving the capacity of public authorities, forest and energy agencies, organisations of forest owners and entrepreneurs and forest advisory organisations to promote the harvest and use of logging residues and small trees cut in early thinning. This handbook consists of five chapters to provide an overview of the role of forest bioenergy in the Baltic Sea region countries – Estonia, Finland, Germany, Latvia, Lithuania, and Sweden. The specific conditions related to each forest growing phase are described from technological, economic, and environmental viewpoints. The handbook provides knowledge on the current harvesting methods in the partner countries and finally recommends best practices for the stakeholders. The aim is to learn about new approaches to the forest bioenergy individually and organisationally.
Keywords: Forest Bioenergy; Harvest Methods; Sustainability; Forest Technology; Forest Bioenergy; Harvest Methods; Sustainability; Forest Technology